INFRARED SPECTROSCOPY OF NEW OXO-CENTRED TRINUCLEAR CARBOXYLATO MIXED-METAL COMPLEXES CONTAINING CrIII 2MnIIIO AND MnIII 2FeIIIO CLUSTERS - E. Karu; R. D. Cannon (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
New mixed-metal complexes CrIII 2MnIIIO and MnIII 2FeIIIO have been prepared and characterized by infrared spectroscopy. The effects of symmetry lowering were observed in the splitting of the νas(M3O) into two components, A1 and B2 modes under C2v. The separation between these modes is rather small in comparison to those of the mixed-metals Fe2 IIIOM11 (M11 = Fe, Ni, Co and Mn), but similar to those of Fe2 IIIMnIIIO, Fe2 IIICoIIIO already reported (Saad, 1990) Vibrational studies in the far I.R would be of interest. Attempts to study the Raman spectra were not possible as the complexes decomposed on exposure to the laser beam.